1997
DOI: 10.1063/1.364378
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative model of volume hologram formation in photopolymers

Abstract: A quantitative model is presented to describe the formation of volume holograms in a polymeric medium containing photopolymerizable acrylate monomers that undergo spatially modulated gelation as a result of exposure to a visible ''write'' beam. The model refines the simple diffusion model of Zhao and Mouroulis ͓J. Mod. Opt. 41, 1929 ͑1994͔͒, by including cure dependence of both the photoreaction kinetics and the monomer diffusivity. These dependences are determined by experimental measurements, using near infr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
133
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 194 publications
(136 citation statements)
references
References 13 publications
(11 reference statements)
3
133
0
Order By: Relevance
“…There are different theoretical models explaining the formation of holograms in photopolymer material [19,20] due to mass transport from dark to bright regions. From the diffusion studies of acrylamide-based photopolymer [21] it was observed that the mass transport from dark to bright regions is faster than in other photopolymer systems [22,23].…”
Section: Theorymentioning
confidence: 99%
“…There are different theoretical models explaining the formation of holograms in photopolymer material [19,20] due to mass transport from dark to bright regions. From the diffusion studies of acrylamide-based photopolymer [21] it was observed that the mass transport from dark to bright regions is faster than in other photopolymer systems [22,23].…”
Section: Theorymentioning
confidence: 99%
“…[6,7] A research challenge of considerable importance concerns the optical shrinkage in the course of hologram formation. [8,9] The photocuring is always linked to shrinkage of the volume, as a result of the shortened particle distance in the covalent bond, compared with the individual van der Waals radii prior to the curing.…”
Section: Introductionmentioning
confidence: 99%
“…The reaction rate and degree of polymerization have been studied 4 by differential scanning calorimetry (DSC), 5 IR absorption spectroscopy, 6,7 fluorescence monitoring during curing, 8 holographic grating formation by UV irradiation and its detection by diffraction. [9][10][11][12][13] Several theoretical models to understand the reaction kinetics have been proposed [14][15][16][17] and the polymerization theory, including monomer diffusion, has been established and used for the explanation of curing. However, the theoretical models are still not enough to cover the actual reactions because of a lack of a detection of the reaction processes.…”
Section: Introductionmentioning
confidence: 99%